Psoriasis and adverse pregnancy outcomes: A nationwide case-control study in 491,274 women in DenmarkCapsule Summary - Cæcilie Bachdal Johansen, MD; Alexander Egeberg, MD, PhD; Espen Jimenez-Solem, MD, PhD; Lone Skov, MD, PhD; Simon Francis Thomsen, MD, PhD (Elsevier, 2022)
Background: The chronic systemic inflammation associated with psoriasis supposedly creates an undesirable milieu for a pregnancy, resulting in an increased risk of adverse pregnancy outcomes (APOs). Objective: To investigate the association between psoriasis and APOs as well as how the association differs according to psoriasis severity (mild and moderate-to-severe). Methods: This nationwide register-based case-control study collected data from 1973 to 2017. Cases were APOs (spontaneous abortion, ectopic pregnancy [EP], intrauterine fetal death, and stillbirth). Singleton live births were controls. Adjusted logistic regression models were used for statistical analyses. Results: In total, 42,041 (8.56%) APOs and 449,233 (91.44%) controls were included. EP was the only APO that was found to be statistically associated with psoriasis (odds ratio, 1.34; 95% CI, 1.06-1.68). Odds ratio for EP was the highest for women with moderate-to-severe psoriasis (odds ratio, 2.77; 95% CI, 1.13-6.76). The absolute risk of EP was 2.48% higher for women with moderate-to-severe psoriasis compared with women without psoriasis (3.98% vs 1.50%). Limitations: No access to clinical data confirming psoriasis severity. Conclusion: The present study found a significant association between EP and psoriasis (absolute risk of 3.98%). As EP is the leading cause of maternal morbidity and mortality in the first trimester of pregnancy, our findings call for particular care for women of reproductive age with psoriasis.